Dampak Ketakutan terhadap Proses Intranatal - Lestari, Selvia; Hermayanti, Yanti; Maryati, Ida (Journal of Telenursing (JOTING), 2023)
This research aims to determine the impact of fear on intranatal and postnatal processes. The research method used was a scoping review of articles about the effects of fear of giving birth by searching database sources from Pubmed, Ebsco, and the Google Scholar search engine. The keywords used for the first search are "Childbirth Fear" AND "Impact of Childbirth Fear" OR "Effects of Childbirth Fear". Research results show that fear of giving birth that continues or is not handled correctly can cause mental well-being disorders after giving birth. These include postnatal anxiety, postnatal depression, and posttraumatic stress disorder. Persistent, unresolved fears can affect the bond between mother and baby. A prolonged fear of giving birth can increase the risk of premature birth or a baby with a low birth weight. The nursing intervention that can be carried out is making a directed and comprehensive birth plan involving the medical and nursing team. In conclusion, fear can trigger a stress response and increase physical and emotional tension in pregnant women during labor, causing delayed delivery or hindering the progression of work. Continued fear can lead to posttraumatic stress disorder, postpartum depression, or difficulty in meeting their baby's emotional and mental needs. Keywords: Maternal Emotions, Fear of Childbirth, Baby Risks